2022
DOI: 10.7759/cureus.22579
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Spectrum of Glomerulonephritis in Medical Renal Biopsies: A Single-Center Study

Abstract: BackgroundGlomerulonephritis is among the most common and serious non-communicable diseases in the world, and some of them are major causes of chronic kidney disease, which eventually leads to kidney failure. In developing countries, it is the most common cause of end-stage renal disease (ESRD). Chronic kidney disease affects 10-16% of the adult population in Asia, including 21.2% in Pakistan. This study aims to determine the frequency and spectrum of glomerulonephritis at our center. MethodologyThis is a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…12,13 The etiological causes of histopathologically confirmed secondary glomerulonephritis are mostly rheumatological diseases, amyloidosis, infections, and malignancies. 14,15 These disorders are accompanied by monoclonal gammopathies or marked by chronic inflammation, causing characteristic changes in SPEP. Therefore, in the present study, we investigated the predictive value of SPEP for classifying glomerular diseases as primary glomerulonephritis (PGn) or SGn.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The etiological causes of histopathologically confirmed secondary glomerulonephritis are mostly rheumatological diseases, amyloidosis, infections, and malignancies. 14,15 These disorders are accompanied by monoclonal gammopathies or marked by chronic inflammation, causing characteristic changes in SPEP. Therefore, in the present study, we investigated the predictive value of SPEP for classifying glomerular diseases as primary glomerulonephritis (PGn) or SGn.…”
Section: Introductionmentioning
confidence: 99%
“…A study revealed that glomerulonephritis is the most common cause of end-stage renal disease in developing countries, and it affects at least 21% of the adult population in Pakistan. 2 The emergence of novel immunotherapeutic approaches may revolutionise treatment outcomes, offering new hopes for patients suffering from this complex and challenging kidney disorder in Pakistan.…”
mentioning
confidence: 99%